Christmas : from solstice to Santa - Tate, Nikki, 1962-; Tate-Stratton, Dani, 1987- (Orca origins., 2018)
Explores the origins of the Christmas holiday, from the pre-Christian Roman and Greek solstice celebrations to the birth of Christ and the story of the Advent, up through history to modern times and different culture's traditions in celebration of Christmas, with food, family, games, fun, and love. Includes a glossary.